Impact of China's OBOR strategy - The impact of China’s belt and road initiative – impacts on dry bulk industry - Sng, Jerry Guan Kiat (2018)
Since 2013, the Belt and Road Initiative (BRI) has constantly been the topic for discussion among many countries. Hailed as “The Project of the Century”, it involved large amount of finances for building of infrastructure in many countries. However, up till date, nothing much has been confirmed and many people are sceptical on the prospect of the BRI. Hence, this project aims to examine the impacts the BRI will bring, as well as the sustainability of the initiative. The project will be split into three parts: 1. The first paper will be focusing on how the BRI impact shipping economically and geopolitically. 2. The second paper will be addressing the impacts of the BRI on the dry bulk industry. 3. The third paper will be investigating on the key challenges of the BRI on ports in Asia. This paper aims to study the benefits of the BRI and the Silk Road Economic Belt (SREB) to the dry bulk industry. It also aims to identify the possible challenges that the BRI will bring to the industry and suggest possible recommendations to curb these challenges.